An Interdependent Approach to Happiness and Well-Being - Uchida, Yukiko; Rappleye, Jeremy (Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
This open access book examines an interdependent approach to happiness and well-being, one that contrasts starkly with dominant approaches that have originated from Western culture(s). It highlights the diversity of potential pathways towards happiness and well-being globally, and answers calls - voiced in the UN's Sustainable Development Goals - for more socially and environmentally sustainable models. Leading global organizations including the OECD, UNICEF, and UNESCO are now proposing human happiness and well-being as a more sustainable alternative to a myopic focus on GDP growth. Yet, the definition of well-being offered by these organizations derives largely from the philosophies, social sciences, and institutional patterns of Europe and the United States. Across seven chapters this book carefully probes the inadequacy of these approaches to well-being globally and reveals the distorting effect this has on how we imagine our world, organize institutions, and plan our collective future(s). It shares a wealth of evidence and examples from across East Asia - a region where interdependence remains foregrounded - and concludes by provocatively arguing that interdependence may provide a more sustainable approach to happiness and well-being in the 21st century. A timely and accessible book, it offers fresh insights for scholars and policymakers working in the areas of psychology, health, sociology, education, international development, public policy, and philosophy. Yukiko Uchida is Professor at Kyoto University, Institute for the Future of Human Society, Japan. From 2019-2020, she was a Fellow at CASBS, Stanford University USA. After receiving her PhD in Social Psychology from Kyoto University in 2003, she worked as a visiting researcher at the University of Michigan and Stanford University. As a Cultural Psychologist, she studies the psychological mechanisms behind the experience of emotions like well-being. Jeremy Rappleye is Associate Professor at Kyoto University, Graduate School of Education, Japan. He received his PhD in Education from the University of Oxford, and since 2012 has worked at Kyoto University in the division of Philosophical Pedagogy. His recent research centers on understanding how diverse institutional patterns (education) derive from different cultural worldviews, with particular focus on conceptualizations of self, (well-)being, and reality.